The pattern of fast food consumption among generation Z in Kota Bharu / Syazwani A. Malek@Abdul Malek … [et al.] - A. Malek@Abdul Malek, Syazwani; Yaacob @ Othman, Azmahani; Chai Li, Cheam; Che Yaacob, Haslina; Ab Rani, Nor Zuriati Amani; Wan Hassan, Wan Hasni (2022)
Fast food is popular among the young generation, especially Generation Z. Eating at fast food restaurants seems to be part of the lifestyle of university students regardless of gender. The fast food diet that is popular among students contains deficient or excess nutrients, which can cause severe nutritional and health consequences such as obesity, diabetes, heart disease and weight control. This study aimed to understand fast food intake patterns among university students, investigate the importance of various factors of the Theory of Planned Behavior by gender and determine whether gender is associated with weight control and fast food intake opportunities. A total of 165 students were involved. Descriptive, independent t-tests and cross-scheduling were used in the study. It was found that 62.7% of the respondents had fast food intake at least once a week. The results of the independent sample t-test and cross-tabulation, on the other hand, showed no significant variation between gender and all key variables. Although there is no relationship between gender and fast food eating patterns, intake among young people is considered high. It is important to target and start from a young age group to reduce the prevalence of unhealthy diets in the country. A program to support good nutritional choices among young people, such as an effective nutrition education program on fast food consumption, could be introduced.